ANTI-MICROBIAL, ANTI-OXIDANT & PHYTOCHEMICAL ANALYSIS oF Citrus aurantium (ORANGE) LEAF EXTRACT - Rao, Nirmala Babu; Kumari, O. Sita; Gajula, Rajesh Goud (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
The present investigation was carried out to evaluate anti-microbial, anti-oxidant and phytochemical compound properties of citrus aurantium leaves. Plants have been the major original source of many drugs used in the treatment of diseases today. Antimicrobial, Antioxidative systems and the contents of phytochemical compounds were investigated in leaves of sour orange trees that are grown under atmospheric co2 concentrations. Phytochemical compounds which are extracted with methanol, ethanol, acetone and distilled water with different medicinal properties. The plant extracts were subjected to preliminary phytochemical screening for the presence of alkaloids, carbohydrates, glycosides, tannins, phenolic compounds, proteins, free amino acids, saponins, phytosterols, and flavonoids. The anti-microbial activity was carried out with two gram positive bacteria i.e., Staphylococcus aureus, Bacillus subtilis and two gram negative bacteria i.e., Escherichia coli, Salmonella typhi by agar well diffusion method. The anti-oxidant properties of these plant extracts of various concentrations (50,150,250 µg/ml) was determined by using methods like DPPH radical scavenging, hydroxyl radical scavenging, superoxide anion, hydrogen peroxide and nitrous oxide the results are compared with known standards. The plant extracts will inhibit free radicals at all concentrations tested. A systematic investigation is carried out to evaluate the total phenolics and flavonoid to explore relation with anti-oxidant properties.